The application of ergative verbs to avoid accusations in the translation of Chinese editorials into English - Dong, Dahui; Yang, Mu-Li (Lingua Posnaniensis, 2018)
The use of ergative verbs results in the agent being backgrounded in an English sentence, and it is often used in the media together with other means such as the use of intransitive verbs, passives, and nominalized nouns to achieve the pragmatic purpose of accusation avoidance. A great deal of research has been done on the role of ergative verbs in media discourse in English as well as the acquisition of ergative verbs by learners of English as a Foreign Language (EFL). However, it remains unclear how EFL Chinese learners of advanced levels of competence, such as postgraduates of translation majors and professional translators, use ergative verbs when translating newspaper editorials from Chinese into English. Nor is it clear whether learners have acquired the requisite knowledge of ergative verbs in order to use them effectively so as to avoid blaming the agent of an action or process in translation. This study recruited 30 native Chinese-speaking translators who fell into three categories: undergraduate translators, graduate translators, and professional translators. A small parallel translation corpus was built, which consisted of 150 English translations of 5 Chinese editorials produced by the translators. Accusation-avoidance expressions in the source text and their translations were then extracted and input into an SPSS spreadsheet. The results show that the use of ergative verbs in translations by undergraduate translators is significantly higher than in translations by graduate and professional translators in terms of quantity. The results of the study may be useful for translation teaching and learning.